PENERAPAN MODEL UTAUT2 UNTUK MENJELASKAN MINAT DAN PERILAKU PENGGUNAAN MOBILE BANKING DI KOTA DENPASAR - Dewi Mas Yogi Pertiwi, Ni Wayan; Ariyanto, Dodik (E-Jurnal Akuntansi, 2017)
Mobile banking is a service provided by the bank to support various banking transactions in order to gain effectiveness and efficiency. Theresearch purpose is to explain the use intention and use behavior of mobile banking through the application of Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. The research took place in Denpasar. The sampling method used accidental sampling. Data were obtained through a survey method with questionnaire technique. Research data analysis used multiple linear regression. The results showed performance expectancyaffects use intention of mobile banking. Habit and use intention affect use behavior of mobile banking.
Keywords: UTAUT2, use intention of mobile banking, use behavior of mobile banking